El relato hesiódico de Pandora y sus incidencias en la cosmogonía ovidiana - Martínez Astorino, Pablo (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
This article studies the Hesiodic influence in the cosmogonic account of Metamorphoses. Once limited the value of philosophical studies about cosmogony, the importance of poetical models has been suggested, particularly that of the Homeric shield of Hephaistos. The relationship with Hesiod, which can be mainly proved through the bond Creation of between the creation of the man and the story of Pandora, shows that Metamorphoses can be read as a continuation of Theogony. And that this work (Metamorphoses) is a corollary of the epic tradition which starts with Homer, by becoming evident, from the beginning, the Ovidian intention of continuing Homer and Hesiod in the same one work.